Training Programs for Managing Well-being in Companies - Treven, Sonja; Treven, Urška; Šarotar Žižek Simona (Naše gospodarstvo/Our economy, 2015)
This paper discussed the significance of well-being (WB) and well-being management (WBM). As successful WBM requires the implementation of different training programs, such programs are presented in detail. The cause–effect relationship between training and individual/organizational performance is researched as well. The aim of the research to support this article was to present WBM, its training programs, as well as the determination of WBM activities concerning the mentioned programs implemented in Slovenian organizations.